Biogas dry reforming over Ni–Ce catalyst supported on nanofibered alumina. (14th August 2020) - González, J.J.; Da Costa-Serra, J.F.; Chica, A.
Abstract: Four catalysts based on Ni and Ni–Ce supported on two γ-aluminas with different morphology (nanofibers and nanograins) have been prepared and studied in the dry reforming of simulated biogas. Catalysts were characterized by N2 physisorption, X-ray diffraction (XRD), temperature-programmed reduction (TPR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), inductively coupled plasma with optical emission spectrometer (ICP-OES), chemisorption of H2 and elemental analysis (EA) to determine their most relevant physicochemical properties. Characterization results show that metallic Ni particles supported on nanofibered alumina (NFA) presents a higher dispersion and smaller size than that supported on the nanograiny alumina (NGA) probably due to the higher mesoporosity presented by the NFA support. On the other hand, the incorporation of Ce has a similar effect than the fibrous morphology, decreasing also the size of the Ni metallic particles and increasing their dispersion. In the dry reforming of synthetic biogas (CH4 /CO2  = 1.5) the nanofibered alumina containing 5 wt% Ni and 1.5 wt% Ce (NiCe/NFA) showed the highest catalytic activity at 750 °C (98% CO2 conversion) and stability (7.7% nickel sinterization level and 2.9 wt% carbon deposition). The stability of this catalyst was also demonstrated at 750 °C during 55 h of reaction time with a loss of activity at the steady state under 2%. In addition, the catalyst was regenerated at 600 °C in oxygen flow, recovering completely its initial catalytic performance. The excellent catalytic behavior of NiCe/NFA material has been related to the fibrous morphology of the alumina support, which promotes a better dispersion of the supported Ni metal particles, decreasing their size and increasing the number of actives sites where dry reforming reaction can take place. In addition, the incorporation of Ce seems to have also an important role by increasing the Ni-support interactions, decreasing sinterization of the metallic Ni particles and coke deposition. The contribution of both effects (morphology and Ce), separately and in combination, have been proved to enhance significantly the catalytic activity and stability of the synthesized catalysts in the dry reforming of simulated biogas. Highlights: Nanograiny and nanofibered γ-Al2O3 with Ni and Ni/Ce have been prepared. They have been studied in the dry reforming of methane. High catalytic activity and stability is exhibited by NiCe/NFA catalyst. The excellent result of NiCe/NFA is related to the small size of it Ni0 particles. Alumina morphology and Ce promote the formation of small Ni0 particles size.